HUBUNGAN SOSIAL MANUSIA USIA LANJUT DALAM KELUARGA DIKAMPUNG AIR TAMBANG KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Warni, WahyunitaWahyunita Warni; Helma, Helma; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
The background of this research based in advance age human problem in relationship with their families such as advanced age human social relationship with couple, child and their grandchild the purpose of this research to describe 1) advanced age human social relationship in family with couple 2) advanced age human social relationship in family with their child, and 3) advanced age human social relationship in family with their grandchild. The kind of this research is descriptive qualitate. This research is done with interview method and observation with 2 people as key informans and 6 people as adding informans are advance age human couple, the child of advance age human and the grandchild of advanced age human at Kampung Air Tambang Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan. Result of the research show that advanced age human social relationship in family is looked from team work and each help between advanced age human with couple, child and their grandchild. After that also is found that there is their habit who do not liked by each other. Advance age human, couple, child, and their grandchild ever liying and each obscure in doing something, they also have different opinions based on the result of this research